Hepatitis B Stigma and Knowledge among Vietnamese in Ho Chi Minh City and Chicago - Lan Dam; Anita Cheng; Phuong Tran; Shirley S. Wong; Ronald Hershow; Sheldon Cotler; Scott J. Cotler (Canadian Journal of Gastroenterology and Hepatology)
Stigma regarding viral hepatitis and liver disease has psychological and social consequences including causing negative self-image, disrupting relationships, and providing a barrier to prevention, testing, and treatment. The aim of this study was to characterize and compare HBV knowledge and stigma in Vietnamese in Ho Chi Minh City and Chicago and to begin to evaluate the cultural context of HBV stigma. Methods. A written survey including knowledge questions and a validated HBV stigma questionnaire was distributed to Vietnamese in Ho Chi Minh City and Chicago. 842 surveys from Ho Chi Minh City and 170 from Chicago were analyzed. Results. Vietnamese living in Chicago had better understanding of HBV transmission and that HBV can cause chronic infection and liver cancer. Vietnamese in Chicago had higher stigma scores on a broad range of items including guilt and shame about HBV and were more likely to feel that persons with HBV can bring harm to others and should be isolated. Conclusions. Vietnamese in Ho Chi Minh City and Chicago have knowledge deficits about HBV, particularly regarding modes of transmission. Persons in Ho Chi Minh City expressed lower levels of HBV stigma than Vietnamese living in Chicago, likely reflecting changing cultural attitudes in Vietnam. Culturally appropriate educational initiatives are needed to address the problem of HBV stigma.